Diverse plant RNAs coat Arabidopsis leaves and are distinct from apoplastic RNAs - M. Lucía Borniego; Meenu Singla-Rastogi; Patricia Baldrich; Megha Hastantram Sampangi-Ramaiah; Hana Zand Karimi; Madison McGregor; Blake C. Meyers; Roger W. Innes (Proceedings of the National Academy of Sciences, 2025)
Transgenic expression of a double-stranded RNA in plants can induce silencing of homologous mRNAs in fungal pathogens. Although such host-induced gene silencing is well documented, the molecular mechanisms by which RNAs can move from the cytoplasm of plant cells across the plasma membrane of both the host cell and fungal cell are poorly understood. Indirect evidence suggests that this RNA transfer may occur at a very early stage of the infection process, prior to breach of the host cell wall, suggesting that silencing RNAs might be secreted onto leaf surfaces. To assess whether Arabidopsis plants possess a mechanism for secreting RNA onto leaf surfaces, we developed a protocol for isolating leaf surface RNA separately from intercellular (apoplastic) RNA. This protocol yielded abundant leaf surface RNA that displayed an RNA banding pattern distinct from apoplastic RNA, suggesting that it may be secreted directly onto the leaf surface rather than exuded through stomata or hydathodes. Notably, this RNA was not associated with either extracellular vesicles or protein complexes; however, RNA species longer than 100 nucleotides could be pelleted by ultracentrifugation. Furthermore, pelleting was inhibited by the divalent cation chelator EGTA, suggesting that these RNAs may form condensates on the leaf surface. These leaf surface RNAs are derived almost exclusively from Arabidopsis, but come from diverse genomic sources, including rRNA, tRNA, mRNA, intergenic RNA, microRNAs, and small interfering RNAs, with tRNAs especially enriched. We speculate that endogenous leaf surface RNA plays an important role in the assembly of distinct microbial communities on leaf surfaces.